Bile Acids Impair Vaccine Response in Children With Biliary Atresia - Liu, Jinchuan; Fei, Yi; Zhou, Tao; Ji, Hao; Wu, Ji; Gu, Xiangqian; Luo, Yi; Zhu, Jianjun; Feng, Mingxuan; Wan, Ping; Qiu, Bijun; Lu, Yefeng; et al. (Frontiers in Immunology, 2021)
Background: Vaccination is the best way to protect children under 5 years from death or disability. Children with biliary atresia (BA), which is the most common pediatric cholestatic end-stage liver disease (PELD), are more vulnerable to infectious diseases. However, the vaccination coverage and factors modulating vaccine responses in children with BA are largely unknown. Methods: In this study, 288 children (median age: 7 months) diagnosed with BA before liver transplantation were enrolled for the evaluation of vaccination status and the factors affecting the immune response to the hepatitis B (HBV) vaccine. Moreover, 49 BA children (median age: 4 months) were enrolled for flow cytometric analysis of CD4+ T cells and CD19+ B cell subsets and correlations with serum bile acid levels. Results: Generally, these children had very low routine vaccination rates for the meningococcal serogroup AC (Men AC) (41.2%), measles-mumps-rubella (MMR) (31.3%), poliomyelitis (Polio) (25.3%), hepatitis A (HAV) (25.0%), Japanese encephalitis (JE) (15.0%), diphtheria-tetanus-pertussis (DTP) (14.2%), meningococcal serogroup A (Men A) (13.5%) and varicella (VAR) (10.8%) vaccines, but not for the HBV (96.2%) and bacillus Calmette-Guérin (BCG) (84.7%) vaccines. Remarkably, 19.8% (57/288) of the patients had HBV infection. Out of 220 patients vaccinated for HBV, 113 (51.4%), 85 (38.6%) and 22 (10%) had one, two or three doses of the HBV vaccine, respectively. Furthermore, logistic regression analysis revealed that the bile acid level was an independent factor associated with poor HBV vaccine response (p = 0.03; OR = 0.394; 95% CI = 0.170-0.969). Immunophenotyping showed that bile acids were only negatively correlated with the CD20+IgG+CD27+ post-class-switched memory B cell ratio (p = 0.01). Conclusion: This study reveals the overall vaccination rates of routine vaccines in Chinese BA children are very low and the poor HBV vaccine responses are associated with bile acids, possibly via the inhibition of class-switched memory B cell response. Clinical Trial Registration: This study was registered at http://www.chictr.org.cn (registration number: ChiCTR1800019165).